Foreign fears? an exploratory study of perceptions and fear of crime in South Africa amongst International students at the University of Cape Town - Mutongwizo, Tariro (Centre for Law and Society, 2026)
The following study is an exploration of international students at the University of Cape Town's perceptions and fear of crime in Cape Town. The study meets three research objectives: an analysis of the fear of crime and its key features; an exploration of international students' perceptions and levels of fear of crime in Cape Town (causes of fear and coping and protective mechanisms); and an assessment of how safety, where it is needed, can be improved. The first objective of the study is met through a literature review. The main features of the fear of crime are reviewed, and the controversial issues surrounding the generators of fear, social profiles of individuals and their fear levels arid the measurement of fear of crime are analysed. The literature review also explores fear of crime from a global and South African context. Victimisation surveys in South Africa as well as efforts in which the curbing of fear has been attempted in the South African context and at the University of Cape Town are also discussed. A questionnaire from a sample of 74 international students at the University of Cape Town meets the second and third objectives of the research. The questionnaire's findings revealthat all the participants considered South Africa to be a high crime society, although very few had actually experienced crime. The generators of fear were mainly from the media and others' victimisation experiences, where participants believed that the causes of crime mainly revolved around poverty and lack of education among the South African population. A greater but limited confidence in Campus Protection Services (CPS) than in the South African Police Services (SAPS) was observed and solutions to the perceived high crime problem on campus were mainly aimed at enclosing the campus and arming CPS. Based on the findings, recommendations are offered to the University of Cape Town, particularly the International Academic Programmes Office (IAPO) and Campus Protection Services (CPS). A recommendation for further study into fear of crime on campuses, among all students and in different communities would also be beneficial for understanding particular group fears and concerns.